ANALISIS KADAR TIMBAL (Pb), SENG (Zn) DAN TEMBAGA (Cu) PADA IKAN BANDENG (Chanos chanos Forsk.) YANG BERASAL DARI LABBAKKANG KAB. PANGKEP SECARA SPEKTROFOTOMETRI SERAPAN ATOM (SSA) - Zulfiah, Azizah; Seniwati, Seniwati; Sukmawati, Sukmawati (Fakultas Farmasi UMI, 2017)
The research was done to analysis of amount lead (Pb), zinc (Zn) and copper (Cu) at milkfish (Chanos chanos Forsk.) from Labbakkang Pangkep by Atomic Absorbtion Spectrophotometry (AAS). Before to be analised, first to do destruction of milkfish (Chanos chanos Forsk.) later on HNO3. Quantitative analysis used atomic absorbtion spectrophotometry (AAS) at wave length of 283,3 nm for lead (Pb), 213,9 nm for zinc (Zn) and 324,8 nm for copper (Cu). Result of research find average rates of lead (Pb) and copper (Cu) from Labbakkang Pangkep is 0,0392 mg/kg and 0,0882 mg/kg. From result of research to showing that average rates Pb and Cu in the location, it is not over from still limit and according to Dirjen POM regulation.